Social impacts of children’s use of the digital world - جامع خلود; ايفا خرما (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The digital world (the Internet) is one of the most important diversities of the contemporary century, and it can reach everywhere, at any time. The Internet reduces the factors of time and space (provided that an electronic device is available and can connect to the Internet); Therefore, we assume the impact of the Internet on people’s lives in general, and on the lives of children in particular. Childhood is one of the stages of life most affected by the environment, and perhaps for some reason it is necessary for you to have the child on you. Childhood emerged as one of the most important stages of character building for people. Today’s children are the youth of the future who will depend on them in the development of an advanced, creative society. With their entry into the digital world, Francesco’s daily has a developer, and you see oversight and are able to prevent them or monitor their entry into this digital world. It has produced many positive effects for us. And cooperation, which is directly or indirectly involved in the formation of many animal, behavioral and cognitive concepts in the child. Children’s digital access to digital learning and well-being is partially monitored by an adult (specific to educators), which leads to tangible positive results, but its use in addition to The female head of the family will lead to bad results, and thus the technical development for everyone, and the access of the Internet to all age groups; It had to work with the children’s category, entering the world digitally and into their consciousness from a Brazilian car; Achieving a healthy personality, and thus achieving a healthy society in the future (a healthy society consists of healthy people.